2007
DOI: 10.21914/anziamj.v47i0.1059
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of non-Newtonian blood flow through a stenosed artery incorporating fluid-structure interaction

Abstract: We investigate fluid and structural responses to pulsatile nonNewtonian blood flow through a stenosed artery, using ansys. The artery was modeled as an axisymmetric stenosed vessel. The wall of the vessel was set to be isotropic and elastic. The blood behavior was described by the Power Law and the Carreau non-Newtonian models, respectively. When compared to the Newtonian flow models, the result from the Carreau model showed very little difference, in terms of velocity, pressure and wall shear stress, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 11 publications
2
25
0
1
Order By: Relevance
“…To simulate the blood flow when the voltage is applied, according to Johnston et al [30,31], who compared five different non-Newtonian blood models, the one that best fitted the experimental data was the Carreau model with the following constants:…”
Section: Numerical Hydrodynamic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…To simulate the blood flow when the voltage is applied, according to Johnston et al [30,31], who compared five different non-Newtonian blood models, the one that best fitted the experimental data was the Carreau model with the following constants:…”
Section: Numerical Hydrodynamic Modelingmentioning
confidence: 99%
“…where λ=3.13s is the time constant, μ is fluid viscosity,γ is strain rate tensor, μ 0 =0.56P is zero strain viscosity (1P=0.1 Ns/m 2 ), μ ∞ = 0.0345P is infinite strain viscosity, and n= 0.3568 is an empirical exponent [30,31].…”
Section: Numerical Hydrodynamic Modelingmentioning
confidence: 99%
“…A number of non-Newtonian viscosity models are adopted in practice for simulating practical flow problems [23][24][25][26]. To simulate blood flow, models such as the Carreau-Yasuda and power law models have been used [25,26].…”
Section: Non-newtonian Modelmentioning
confidence: 99%
“…To simulate blood flow, models such as the Carreau-Yasuda and power law models have been used [25,26]. Cho and Kensey [27] investigated several non-Newtonian models, including power law and Carreau models, to represent the rheological behaviour of the blood.…”
Section: Non-newtonian Modelmentioning
confidence: 99%
“…They assumed blood as a Newtonian fluid, studied the flow characteristics such as the velocity and the wall shear stress, and observed that the expansion of the arteries is due to the internal pressure. Chan et al [8] continued Lee and Xu's study [6] , and considered the power law and Carreau non-Newtonian models for the blood flow. Li et al [9] studied the pulsatile blood flow and the vessel wall mechanics with different degrees of stenoses.…”
Section: Introductionmentioning
confidence: 99%